The analyses of length and type of bladder injury during cesarean section in patients with or without placenta accreta: a retrospective case-control study - Fikriye Işıl Adıgüzel; Cevdet Adıgüzel; Gülsüm Uysal; Mert Ali Karataş (BMC Pregnancy and Childbirth)
Abstract Aim To evaluate the outcomes of patients with bladder injury during cesarean delivery with or without placenta accreta spectrum (PAS). Materials ant method Retrospective case series of all pregnancies complicated by bladder injury during cesarean delivery were evaluated in a tertiary hospital between January 2018 and December 2023. Data of patients’ demographic and obstetric parameters including bladder injury, such as length and degree of bladder injury, time of bladder injury occurrence (during entrance of peritoneal cavity, bladder flap dissection, uterine incision, or delivery) were all recorded. Patients with bladder injury were also divided into two group as with PAS (+) or without PAS (-), recorded data were compared between groups. Results Bladder injury was detected in 72 (0.02%) of 35,465 total cesarean section operations. There were 45 (7.5%) patients with bladder injuries in the PAS group. The mean length of bladder injury (cm) in PAS (+) group and PAS (-) group were 5.20 ± 1.98 and 3.74 ± 1.63, respectively (p = 0.002). The gestational age at delivery and birth weight were significantly higher in PAS (-) group, while hospital stay was longer in PAS (+) group. The occurrence of bladder injury during flap dissection was significantly higher in PAS (+) group. However, in PAS (-) group the bladder injury during uterine incision or delivery was significantly higher (p < 0.001). The bladder injury rates in emergency cesarean sections were higher in two groups than elective cases. Conclusions The risk of bladder injury is higher in emergency cesarean sections, regardless of PAS status. Longer and more severe bladder injuries are seen in the PAS group.